1987
DOI: 10.1073/pnas.84.24.8956
|View full text |Cite
|
Sign up to set email alerts
|

An activated c-Ha-ras allele blocks the induction of muscle-specific genes whose expression is contingent on mitogen withdrawal.

Abstract: During myogenesis, induction of muscle-specific genes is subject to negative control by polypeptide mitogens and type-13 transforming growth factor. Since transduction of growth factor signals may require proteins encoded by cellular ras oncogenes, we have tested whether a mutationally altered Harvey ras expression vector, by itself, can prevent establishment of a differentiated phenotype in BC3H1 mouse myoblasts. Transfection with the valine-12 allele of the human Harvey ras gene, under the control of its own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 45 publications
5
59
1
Order By: Relevance
“…Blocking essentially all autocrine growth loops with suramin, a general growth factor antagonist, however, inhibited both proliferation and restored the myogenic phenotype (Giovanni et al, 1995). The ®nding that the degree of proliferation is not inversely proportional to the degree of di erentiation is not surprising since it is well documented that the inhibition of di erentiation by growth factors or by oncogenic Ras is independent of their mitogenicity Olson et al, 1987;Payne et al, 1987;Gossett et al, 1988;Lathrop et al, 1985;Rosenthal and Cheng, 1995;Weyman et al, 1997). It is somewhat intriguing, however, that blocking both FGF-2 and IGF does not revert the di erentiation-defective phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking essentially all autocrine growth loops with suramin, a general growth factor antagonist, however, inhibited both proliferation and restored the myogenic phenotype (Giovanni et al, 1995). The ®nding that the degree of proliferation is not inversely proportional to the degree of di erentiation is not surprising since it is well documented that the inhibition of di erentiation by growth factors or by oncogenic Ras is independent of their mitogenicity Olson et al, 1987;Payne et al, 1987;Gossett et al, 1988;Lathrop et al, 1985;Rosenthal and Cheng, 1995;Weyman et al, 1997). It is somewhat intriguing, however, that blocking both FGF-2 and IGF does not revert the di erentiation-defective phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while treatment of 23A2 myoblasts with either FGF-2 or IGF-1 inducs a slight increase in the incorporation of thymidine into newly synthesized DNA, treatment of 23A2 myoblasts with A2:H-Ras conditioned DM does not (d.n.s.). The ®nding that A2:HRas conditioned DM blocks 23A2 myoblast differentiation without inducing proliferation is not surprising since it is well documented that the inhibition of di erentiation by growth factors or by oncogenic Ras does not rely on their mitogenic potential Olson et al, 1987;Payne et al, 1987;Gossett et al, 1988;Lathrop et al, 1985;Rosenthal and Cheng, 1995;Weyman et al, 1997).…”
Section: A2:h-ras Conditioned Media Does Not Mimic the Actions Of Fgfmentioning
confidence: 99%
“…Previous reports have shown that most Ras-family GTP-binding proteins, such as H-Ras, N-Ras, Rap1 and TC21, inhibit skeletal muscle dierentiation Payne et al, 1987;Konieczny et al, 1989;Lassar et al, 1989;Pizon et al, 1999;Graham et al, 1999). The Ras-regulated signaling pathways leading to the inhibition of myogenesis are being clari®ed.…”
Section: Discussionmentioning
confidence: 99%
“…The dierentiation is also inhibited by expression of several oncogenes such as myc, fos, jun and ras (Olson, 1992). It is well-established that oncogenic Ras inhibits skeletal myogenesis, probably through mimicking signaling events exerted by growth factors Payne et al, 1987;Konieczny et al, 1989;Lassar et al, 1989). In addition to Ras, two other Ras-family proteins, Rap1 and TC21, also block skeletal myogenesis (Pizon et al, 1999;Graham et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to promoting tumor formation, anchorage-independent growth, and cellular immortalization, expression of transforming oncogenes inhibits cellular differentiation in several different cell lineages. In muscle cells, expression of oncogenic tyrosine kinases (v-src and v-fps), growth factor receptors (v-erbB), nuclear oncogene products (v-myc, c-myc, v-erbA, and E1A), and the activated forms of signal-transducing G proteins (H-ras and N-ras) can inhibit terminal differentiation to various extents (5,7,10,14,30,31,37,45). We previously demonstrated that ras and fos prevent myogenesis by inhibiting expression of MyoD (19).…”
Section: Discussionmentioning
confidence: 99%